A Systematic Review on the Emotional Dimensions of Music Education - Váradi, Judit; Szűcs, Tímea; Kerekes, Rita; Kiss, Julianna; Radócz, József Miklós (Harmonia: Journal of Arts Research and Education, 2024)
In the constantly changing challenges of education, the role of emotional competence is becoming increasingly important. This paper explores the literature on the connections between music and emotional education at different levels of education and in teacher training, and in light of the results, it presents the possibilities of music education in the development of different dimensions. This study uses a systematic literature review procedure prepared according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The acquisition, effective recognition, and management of emotions are necessary knowledge, skills, and attitudes that help individuals develop and maintain functioning social relationships and make responsible decisions. The role of music in education has come to the fore several times in the past centuries. Music education can convey emotions and contribute to socio-emotional education and mental well-being.